Demystifying the two-sided role of inorganic halides in the structure and performance of Ziegler–Natta catalysts. Issue 12 (28th September 2022) - Jandaghian, Mohammad Hossein; Maddah, Yasaman; Hosseini, Shahin; Eshaghzadeh, Fahimeh; Sepahi, Abdolhannan; Nikzinat, Ehsan; Masoori, Maryam; Bazgir, Hossein; Rashedi, Reza
Abstract : Inorganic halide additives can act as dopants and/or chlorine-donating species in Ziegler–Natta recipes. Abstract : In this paper, the results of adding SiCl4 (as a model inorganic halide) to the formulation of an industrially well-known Ziegler–Natta catalyst (ZNC) have been investigated to shed light on the hidden sides of the catalysts. Four different ZNCs, which differ only in the addition steps, were synthesized and fully characterized using numerous techniques. Furthermore, the catalysts were used for the production of a set of monomodal and bimodal ethylene/1-butene copolymers. Finally, differential scanning calorimetry (DSC), successive self-nucleation annealing (SSA), and some rheological tests were carried out on the synthesized copolymers to reveal the roles of SiCl4 in the molecular architecture of polyolefins made using the ZNCs. The results showed that inorganic halides play two different roles depending on the stage of their addition during the ZNC synthetic procedure. Firstly, adding the inorganic halide before the main chlorination phase can increase the active centers' binding energy (BE) by 0.4–0.8 eV, which can be interpreted by considering an electron-poorer environment around the centers. In other words, in this case, SiCl4 can be doped into the structure of MgCl2, and it led to a 30% to 60% reduction in the amount of hexane-soluble fractions and fine particles produced during copolymerization reactions. On the other hand, the addition of SiCl4 after the chlorination phase resulted in a 0.4 eV reduction in the BE of titanium species, which means that, in this case, the inorganic halide can enrich the electronic states of active centers without doping into the structure of MgCl2 . By doing so, a dramatic change occurred in the stereospecificity of the produced copolymeric chains, leading to a jump of about 10–30% in the strain hardening modulus of the final copolymers.